2014
DOI: 10.3233/rnn-139013
|View full text |Cite
|
Sign up to set email alerts
|

Learning, memory and brain plasticity in posttraumatic stress disorder: Context matters

Abstract: We review evidence from our laboratory that suggests that in addition to enhanced cue conditioning and delayed cue extinction disturbed contextual learning may play an important role in the development and maintenance of posttraumatic stress disorder. Based on data from a longitudinal sample of rescue workers at high risk for posttraumatic stress disorder and data on single trauma exposed persons with and without posttraumatic stress disorder we show the crucial role of the hippocampus for contextual memory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
1
10
0
2
Order By: Relevance
“…In addition, they found a strong negative correlation of 0.65 between WM in the anterior, central and total FA of the CC for the mean association reaction time for pictures. These findings indicate a deficit in associative encoding and memory, which is in line with the idea of a disturbance of brain circuits involved in contextual processing in PTSD ( Bisby and Burgess, 2017 ; Brewin et al, 2010 ; Flor and Nees, 2014 ; Liberzon and Abelson, 2016 ). In their review, Daniels et al (2013) observed a reduced volume of the CC in the majority of studies investigating trauma-exposed children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, they found a strong negative correlation of 0.65 between WM in the anterior, central and total FA of the CC for the mean association reaction time for pictures. These findings indicate a deficit in associative encoding and memory, which is in line with the idea of a disturbance of brain circuits involved in contextual processing in PTSD ( Bisby and Burgess, 2017 ; Brewin et al, 2010 ; Flor and Nees, 2014 ; Liberzon and Abelson, 2016 ). In their review, Daniels et al (2013) observed a reduced volume of the CC in the majority of studies investigating trauma-exposed children.…”
Section: Discussionsupporting
confidence: 88%
“…PTSD is characterized by symptom clusters such as re-experiencing the traumatic event, avoidance and numbing, hyperarousal and negative thought and mood changes (Diagnostic and Statistical Manual of Mental Disorders (DSM) 5; American Psychiatric Association, 2013 ). In the past decades, theoretical frameworks have identified several key brain circuits involved in different cognitive and emotional processes contributing to the development of PTSD with a focus on disturbed contextual processing, an inability to extinguish aversive memories and an increase in threat detection and arousal ( Bisby and Burgess, 2017 ; Brewin et al, 2010 ; Ehlers and Clark, 2000 ; Flor and Nees, 2014 ; Jacobs and Nadel, 1985 ; Liberzon and Abelson, 2016 ; Maren et al, 2013 ). Patients with PTSD have trouble to contextualize incoming visual-spatial information, which is associated with a functional down regulation in activity in the medial temporal lobe (MTL), most prominently in the hippocampus, and the retrosplenial cortex (RSC), which translates this information into a coherent egocentric mental image in the precuneus ( Bisby and Burgess, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, following the involvement in a traffic accident, environmental cues that were associated with the event (e.g., the make of the car, the color of surrounding vehicles, the song being played on the radio when the collision had occurred) may reactivate strong emotional memories, upon exposure to such cues at a later time. Furthermore, such associative mechanisms seem to be compromised in some clinical conditions, such as posttraumatic stress disorder (PTSD), in which events associated with traumatizing contexts can involuntarily trigger vivid recollection of distressing memories in the form of intrusive thoughts, flashbacks, or nightmares ( Flor and Nees, 2014 ; Wilker et al, 2014 ). Therefore, recent research has begun to examine the impact of emotion on memory for items as a part of, or in relation to, other items ( Chiu et al, 2013 ).…”
Section: Emerging Directions In Emotional Episodic Memorymentioning
confidence: 99%
“…Memory dysfunctions in PTSD showed a remarkable amelioration after CBT, and PAL improvement was associated increased blood FKBP5 mRNA expression. Although numerous studies have reported impaired declarative memory in PTSD [22][23][24][25][26], this is the first study showing that CBT may boost memory. The fact that PAL was associated with FKBP5 expression is not surprising, assuming that both are closely related to the hippocampus: PAL is a prototypical test for hippocampal functioning [20] and enhanced FKBP5 may be associated with the regeneration of hippocampal networks in PTSD [9].…”
Section: Discussionmentioning
confidence: 96%